Long‐term mortality after acute coronary syndromes among patients with normal, mildly reduced, or reduced ejection fraction. (23rd October 2022) - Furtado, Remo H.M.; Juliasz, Marcela G.; Chiu, Felipe Y.J.; Bastos, Livia B.C.; Dalcoquio, Talia F.; Lima, Felipe G.; Rosa, Renato; Caporrino, Cesar A.; Bertolin, Adriadne; Genestreti, Paulo R.R.; Ribeiro, Andre S.; Andrade, Maria Carolina; et al.
Abstract: Aims: Left ventricular ejection fraction (LVEF) ≤ 40% is a well‐established risk factor for mortality after acute coronary syndromes (ACS). However, the long‐term prognostic impact of mildly reduced ejection fraction (EF) (LVEF 41–49%) after ACS remains less clear. Methods and results: This was a retrospective study enrolling patients admitted with ACS included in a single‐centre databank. LVEF was assessed by echocardiography during index hospitalization. Patients were divided in the following categories according to LVEF: normal (LVEF ≥ 50%), mildly reduced (LVEF 41–49%), and reduced (LVEF ≤ 40%). The endpoint of interest was all‐cause death after hospital discharge. A multivariable Cox model was used to adjust for confounders. A total of 3200 patients were included (1952 with normal EF, 375 with mildly reduced EF, and 873 with reduced EF). The estimated cumulative incidence rates of mortality at 10 years for patients with normal, mildly reduced, and reduced EF were 24.8%, 33.5%, and 41.3%, respectively. After adjustments, the presence of reduced EF was associated with higher mortality compared with normal EF [adjusted hazard ratio (HR) 1.64; 95% confidence interval (CI) 1.36–1.96; P  < 0.001], as was mildly reduced EF compared with normal EF (adjusted HR 1.33; 95% CI 1.05–1.68; P  = 0.019). The presence of reduced EF was not associated with a statistically significantly higher mortality compared with mildly reduced EF (adjusted HR 1.23; 95% CI 0.96–1.57; P  = 0.095). Conclusions: In patients with ACS, mildly reduced EF measured in the acute phase was associated with higher long‐term mortality compared with patients with normal EF. These data emphasize the importance of anti‐remodelling therapies for ACS patients who have LVEF in the mildly reduced range.